Evaluation of Sleep Quality in Asthmatic Children with the Paediatric Sleep Questionnaire (PSQ) - Mehmet Yaşar Özkars; Seda Çevik; Serap Ata; Alican Sarısaltık; Uğur Altaş (MDPI AG, 2024)
Considering the high prevalence of sleep-related breathing disorders (SRBD) in asthmatic patients, we aimed to compare asthmatic children and healthy children in terms of SRBD according to Paediatric Sleep Questionnaire (PSQ) scores. A questionnaire covering sociodemographic characteristics of the patients and the PSQ, which evaluates sleep quality and consists of 22 questions, was administered. During the data collection process, 180 patients in the patient group and 170 patients in the control group were included. The patient group showed statistically significantly higher total scores and subscale scores for snoring, sleepiness, and inattention compared to the control group. Statistically significant correlations were found between the sleepiness subscale and body mass index z score in a negative direction and between age at presentation and duration of asthma in a positive direction. Our findings endorse employing the PSQ as a screening instrument in the outpatient environment to ensure timely referral of asthma patients to a sleep specialist for SRBD evaluation. Considering the widespread occurrence of snoring and asthma, this tool could aid in identifying patients with an elevated risk of SRBD and expedite the scheduling of nocturnal polysomnography for these children.